Linking ROS Levels to Autophagy: The Key Role of AMPK - Francesco Agostini; Marco Bisaglia; Nicoletta Plotegher (MDPI AG, 2023)
Oxygen reactive species (ROS) are a group of molecules generated from the incomplete reduction of oxygen. Due to their high reactivity, ROS can interact with and influence the function of multiple targets, which include DNA, lipids, and proteins. Among the proteins affected by ROS, AMP-activated protein kinase (AMPK) is considered a major sensor of the intracellular energetic status and a crucial hub involved in the regulation of key cellular processes, like autophagy and lysosomal function. Thanks to these features, AMPK has been recently demonstrated to be able to perceive signals related to the variation of mitochondrial dynamics and to transduce them to the lysosomes, influencing the autophagic flux. Since ROS production is largely dependent on mitochondrial activity, through the modulation of AMPK these molecules may represent important signaling agents which participate in the crosstalk between mitochondria and lysosomes, allowing the coordination of these organelles' functions. In this review, we will describe the mechanisms through which ROS activate AMPK and the signaling pathways that allow this protein to affect the autophagic process. The picture that emerges from the literature is that AMPK regulation is highly tissue-specific and that different pools of AMPK can be localized at specific intracellular compartments, thus differentially responding to altered ROS levels. For this reason, future studies will be highly advisable to discriminate the specific contribution of the activation of different AMPK subpopulations to the autophagic pathway.